Learner perceptions of successful engagement in undergraduate computer science education : a grounded theory - Huggard, Meriel Olwen (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2013)
Computer science degree programs have proliferated due to the demands of industry and the pressures placed on higher education institutions by national governments. In tandem with this, the technological familiarity presumed in most undergraduate degree programs has also increased significantly, particularly in the Engineering and Science based disciplines. The computer science skills that these students are assumed to have, or are expected to acquire and develop, span a very broad spectrum of computer-based engagement. Many studies have highlighted the significant percentages of students who start degree programs in these areas and then fail to progress beyond the first year. Universities have been required to engage with, and address, the fundamental challenges facing these students and to support their successful progression throughout their undergraduate careers.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin